PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA SUBTEMA BANGGA TERHADAP DAERAH TEMPAT TINGGALKU - Yunida Devitasari; Rais Hidayat; Dadang Kurnia (Universitas Pakuan, 2018)
Application of Problem Based Learning model to improve the learning outcomes proudly in the area where I live. Thesis study program of elementary school teacher education faculty teacher and education Pakuan Bogor Univercity 2018. This study with the design and model of Classroom Action Research (CAR) Conducted Collaboratively Between Researchess and observer and the subject studied. The purpose proud subtheme learning outcomes to my area of reasidence in grade 4 through the application of Problem Based Learning model. The subject of this research is the 4th grader of the public elementary school 01 Nagrak Gunung Putri district of Bogor Consisting of 39 students the implementation of this research is carried 2017/2018. The results showed that the average value of the learning process assessment in the cycle I of 78,25, cycle II 83,5 and the cycle III 90 with success indicators that is 81, observation cycle I of 60,9, cycle II 76,09 and cycle III 93,17 achievement indicator that is 81. Completeness of students learning result cycle I reach 36%, cycle II 64,11% and cycle III equal to 92%indicator of success 75% KKM value 75 based on the results of this studies, it can be concluded that the application of problem based learning model can improve the process of learning process and improve learning outcomes on proud subtema to my residence in grade 4 student of the public elementary school 01 Nagrak Gunung Putri district of bogor in the even semester of the academic year 2017/2018. Keywords: Learning Outcomes, Problem Based Learning model, the learning outcomes proudly in the area where I live